Geomorphological mapping as a tool for environmental management: a case study in the municipality of São Benedito, Ceará, Brazil - Lopes, Maria Vitória Rodrigues; Sobrinho, José Falcão (Sociedade & Natureza, 2025)
Recognizing the current global situation regarding the crises caused by climate change, land use planning is seen as a tool with high potential for adapting to and mitigating the effects of such changes on natural elements, as well as a way to prevent environmental degradation (Ross, 2006). This study, aimed at supporting the planning and land use planning of São Benedito, a municipality located on the Ibiapaba Plateau in the state of Ceará, conducts geomorphological mapping based on Ross's (1992) methodology. To this end, climatic, pedological, and geological mapping is consulted, correlated with data from the last demographic census, and the forms and types of land use and occupation are analyzed through field visits. Six units with similar landform patterns were mapped for the municipality, distinguishing sixteen landform types, varying among denudational, flattened, and aggradational forms. By specifying the predominant processes in each unit, detailing relief characteristics provided by the active processes, we sought to generate knowledge about the geomorphological diversity on the Ibiapaba plateau and, above all, to support possible environmental planning initiatives in the municipality.